2010
DOI: 10.1111/j.1600-0536.2010.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational allergic contact dermatitis from tetrazepam in nurses

Abstract: Occupational airborne and/or hand contact dermatitis from tetrazepam might be much more common than suspected by dermatologists, particularly in view of the short period in which all cases have been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In this study, we did not examine the health effects of chronic exposures to PM from pill crushing, but studies have shown correlations between crushing benzodiazepine, beta-blockers, ACE inhibitors, trazodone, ranitidine, and zolpidem and the development of airborne occupational contact dermatitis in nurses (Gilissen et al, 2020; Hulst et al, 2010; Swinnen et al, 2014). It is critical to note that allergic reactions may result from exposure to inactive ingredients of oral medications (Abrantes et al, 2016; Kelso, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we did not examine the health effects of chronic exposures to PM from pill crushing, but studies have shown correlations between crushing benzodiazepine, beta-blockers, ACE inhibitors, trazodone, ranitidine, and zolpidem and the development of airborne occupational contact dermatitis in nurses (Gilissen et al, 2020; Hulst et al, 2010; Swinnen et al, 2014). It is critical to note that allergic reactions may result from exposure to inactive ingredients of oral medications (Abrantes et al, 2016; Kelso, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Her symptoms continued for several months but resolved when exposure to clozapine powder was stopped (Lewis et al, 2012). Multiple studies show the correlation between crushing benzodiazepine medications and nurse development of airborne occupational contact dermatitis (Gilissen et al, 2020; Hulst et al, 2010; Swinnen et al, 2014), but other drugs have also been correlated with contact dermatitis, such as beta-blockers, Angiotensin-converting enzyme (ACE) inhibitors, trazodone, ranitidine, and zolpidem (Gilissen et al, 2020; Swinnen et al, 2014). The allergic reactions might result from exposure to inactive ingredients of oral medications (Abrantes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, tetrazepam has triggered hand and facial dermatitis [27,28]. Of note, there may be significant cross-sensitization to other benzodiazepines, which in turn demonstrates the importance of through patch testing and consideration of cross-reactors.…”
Section: Medicationsmentioning
confidence: 99%